Comparison of the percentage of NRBC/100 WBC in early onset sepsis and Non-Infectious premature infants - Hassan Boskabadi (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
AbstractIntroduction: In spite of significant advances in medical care, neonatal sepsis remains an important risk factor for neonatal morbidity and mortality. Accordingly, the present study was conducted to compare the number of Nucleated Red Blood Cells per 100 white blood cells (NRBC/100WBC) in neonates with early onset sepsis and non-infectious neonates.Materials and Methods: In this cross-sectional study, of 154 neonates admitted to the NICU of Ghaem Hospital in Mashhad, Iran within the first three days of life, during 2014 to 2018, the characteristics of 44 neonates identified early onset sepsis (Case group) were compared with 110 non-infectious neonates (Control group). After the confirmation of sepsis in neonates based on positive blood culture and laboratory results, a researcher-made questionnaire containing neonatal characteristics (gestational age, weight, first minute Apgar scores, fifth minute Apgar score, duration of oxygen therapy, and mechanical ventilation duration) and neonatal laboratory profiles (Cord blood samples CBC (complete blood count), Absolut NRBC/mm3, NRBC/100 WBC and CRP) was filled in.Results: The results of this study showed that the absolute number of NRBC/mm3 in control group was 56.07±86.65and in case group was 592.70±1166.75 (p = 0.000). Also, the number of NRBC per 100 white blood cells in control group was 6.54±11.18and in case group was 31.84±40.07 (p = 0.000). The absolute number of NRBC/mm3 for the detection of early onset sepsis had a good sensitivity (78%) and NRBC/100WBC was suitable specificity (68.2%).Conclusion: This study indicated that NRBC/100 WBC and absolute NRBC count/mm3 can be helpful in the diagnosis of early onset sepsis and have an acceptable sensitivity and specificity.Keywords: Early onset Sepsis; Nucleated Red Blood Cells [NRBC]; Neonates, Blood culture